Empowering Senior Santri as Peace Educators: Developing a Community-Based Peer Mentorship Model to Prevent Violence in Islamic Boarding Schools - Muchasan, Ali; Salim Ashar; Moch Naufal (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2026)
Background: This study addresses the critical social issue of violence and bullying within Islamic educational institutions. It focuses on the role and potential of senior santri (students) as peer mentors in Islamic boarding schools (pesantren) in Kediri, Indonesia, to act as agents of peace and change. Purpose of the Study: The purpose is to examine how values grounded in education and empathy can mitigate violence, specifically through the peer mentoring practices of senior santri. The objective is to understand the nature of this mentorship to inform the development of a community-based violence prevention model. Methods: This community service program (Pengabdian kepada Masyarakat - PkM) employs a participatory action research (PAR) approach and a qualitative phenomenological design. The method involved collaborative engagement with ten senior santri through participatory observation, in-depth interviews, and documentation. Data were analyzed using the Moustakas phenomenological method. Results: The analysis identified seven core themes defining the mentorship, including its role as moral leadership, a shift from authority to empathy, and its function as a reflective, spiritual practice for violence prevention. The findings position peer mentorship as a foundational element for humanistic education (tarbiyah Islamiyah) and provide a basis for developing ethical training models to foster safe, non-violent educational environments.